(3GdOQIs - (3GdnqWnHGnWnHGFj GdHQhLQOj, GHf GdeQJVi, HMQ GdYdhe, eMeO egOj Hf eQJVi Hf eMeO, J (B1212 (3g`s
(3ChdgG (B:s
(3ChdgG(B: (3GaJJM GdebGd HYO GdHSedI (B*** (3HMeO NjQ efYe hGdTcQ dg (B... (3GdeGA eG Sej eGA eWdbG (B*** (3aVdG Ydi GdfGS WghQG NdbGs
(3BNQgG (B:s
(3BNQgG(B: (3hde CLO ddSQ hGdCLgGQ (B*** (3fUG LG aCfJ HGdNjGQ (B*** (3hGOY YbjH GdaQV HGdeCKhQ (B*** (3ef GdOYGA GdehLR GdeTghQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe, L (B7: 113s
(3GdPQjYI, L (B8: 67(3, L (B13:(3; (B143s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis